A POLÍTICA DE COTAS NO TRABALHO COMO AÇÃO AFIRMATIVA PARA A PESSOA COM DEFICIÊNCIA EM SÃO LUÍS-MA - Maciel Júnior, João da Silva (2008)
This master's degree dissertation in Public Politics approaches the notion of person with deficiency, equality of chances, discrimination against the person with deficiency, affirmative action, the right To the difference for the politics of quotas in the used companies with one hundred or more (in the terms of the Federal Law nº 8,213/91 and art. 35 of Federal the Decree nº 3,298/99) in the perception of the great employers and the people with deficiency in São Luís of the Maranhão. It takes for empirical field the obliged local companies to fulfill to the politics of quotas and the representatives of public agencies DRT-MA, MPT-MA, SINE-MA, INSS and MPE, of the Advice of Right, ONGs, the social movements and workers with deficiency. This study it adopts for secular clipping the period enters the year of 2000 until October of 2007. The study if it initiates with a boarding of the deficiency in the legal panorama and the public politics, analyzing the reception of Conventions nº the 111/58 and nº 159/83 of the OIT in Brazil and the National Plan of Human Rights to the light of the National Politics of Integration of the Carrying Person of Deficiency and if it deepens when approaching the paradigms of attention to the person with deficiency in Brazil comparing with the context place. Later it approaches the politics of quotas in the companies as instrument of the National Politics of Integration of the "Carrying Person of Deficiency" (Law nº 7,853/89) in Is Luís-MA and the vision of its diverse local citizens. It concludes pointing that, even so it has registered diverse conceptual advances and practical also in the local context, the politics of quotas in the companies implemented as affirmative action under the responsibility of the DRT-MA still did not obtain to fulfill its objective declared in São Luís, which is: to eliminate all distinction, exclusion or preference that have for effect annular or to modify the equality of chances in the inserting, profession or employment relationship in the companies with more than 100 used the carrying people of deficiency and the workers rehabilitated for the social welfare.